2013
DOI: 10.4028/www.scientific.net/kem.535-536.227
|View full text |Cite
|
Sign up to set email alerts
|

Application of Indentation Size Effect in Finite Element Analysis for Friction Simulation

Abstract: Contact simulation involving asperities was developed by assuming that the deformation by asperities is equivalent to the deformation by an indenter in a hardness test. Consequently, depth dependent flow stress curves were derived from the indentation size effect model from Abu Al-Rub and were used to simulate the influence of the number of asperities involved during contact on the distribution of contact pressure and the value of effective friction coefficient. Results from simulations suggested that multiply… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In a previous study with conical asperity [10], it was shown that the measured friction during the simulation is lower when the depth-dependent flow stress is introduced. More importantly, the influence of indentation size effect model is stronger in smoother surface.…”
Section: Introductionmentioning
confidence: 93%
“…In a previous study with conical asperity [10], it was shown that the measured friction during the simulation is lower when the depth-dependent flow stress is introduced. More importantly, the influence of indentation size effect model is stronger in smoother surface.…”
Section: Introductionmentioning
confidence: 93%